Feeding preference as a main determinant of microscale patchiness among terrestrial nematodes. (21st April 2017) - Quist, Casper W.; Gort, Gerrit; Mulder, Christian; Wilbers, Ruud H. P.; Termorshuizen, Aad J.; Bakker, Jaap; Helder, Johannes
Abstract: Soil biota are responsible for essential ecosystem services such as carbon storage, nutrient cycling and water retention. However, assessment of the condition of soil biota is hampered by an overwhelming level of diversity. With representatives in all trophic levels of the food web, nematode communities can be used as bioindicators. Accurate assessment of nematode assemblages requires insight into the distribution of specimens with distinct food preferences. With the availability of taxon‐specific quantitative PCR assays, distribution patterns of multiple nematode groups can be investigated simultaneously. Here, microscale patchiness of 45 nematode taxa was studied on 12 sampling sites (each with four adjacent microplots) located on arable fields or semi‐natural grasslands ('system'), and on marine, river clay or sandy soils ('soil type'). From each microplot, five composite samples were collected. Contrary to our expectations, an increase in the number of cores per composite sample did not result in more accurate measurements, and apparently the levels of microscale patchiness of the taxa are low compared to what has been reported for oligophagous plant‐parasites. System and soil type did not affect microscale distribution. To investigate the level of patchiness in more detail, detection probability (DP) and variability of abundances were calculated. Common and widespread bacterivorous and fungivorous taxa had DP ≥ 90%, confirming low level of microscale patchiness. With DPs of 40%–70%, predators and most omnivores showed degrees of local clustering. An overview of mean variabilities of abundances is presented that offers insight into how feeding preferences impact the microscale distribution both between and within trophic groups.